Predicting how individuals approach enrichment: Regulatory focus in cotton‐top tamarins (Sanguinus oedipus). Issue 4 (6th May 2013) - Franks, Becca; Reiss, Diana; Cole, Patricia; Friedrich, Volney; Thompson, Nicole; Higgins, E. Tory
Abstract Evidence is mounting that personality is associated with health and well‐being in humans and other animals. In a step towards increasing our understanding of this link, we applied regulatory focus theory, a motivational perspective from social psychology, to the behavior of zoo‐housed cotton top tamarins. We tested whether regulatory focus "personality, " that is stable differences in whether an individual is motivated by gains versus safety, would 1) produce individual differences in behavior and 2) predict how individuals interact with enrichment. First, we characterized individuals with respect to several key behaviors: eating in the open, hiding, and time spent near the front of the exhibit. The monkeys were consistent in their behavioral tendencies across the 6‐month study, allowing regulatory focus classification. One monkey showed evidence of being a promotion‐individual, that is, more motivated by gains than safety. One monkey showed evidence of being a prevention‐individual, that is, more motivated by safety than gains. The other monkeys were stable in their behavior and showed evidence of being intermediate‐individuals, that is, they favored neither gains nor safety. Using these characterizations, we predicted distinct patterns of individual‐object interactions with enrichment. For example, we predicted that a promotion‐individual (favoring gains over safety) would approach potential gains faster than a prevention‐individual (favoring safety over gains). Counter‐intuitively, however, we also predicted that a promotion‐individual would approach non‐gains slower than a prevention‐individual concerned with safety. We found support for our predictions, which suggests that regulatory focus theory could be a useful tool for understanding how and why individuals interact with environmental enrichment. Zoo Biol. 32:427–435, 2013. © 2013 Wiley Periodicals Inc.